Revising the oldest Oldowan: Updated optimal linear estimation models and the impact of Nyayanga (Kenya) - Alastair Key; Tomos Proffitt (Journal of Human Evolution, 2024)

Homo floresiensis and Homo luzonensis are not temporally exceptional relative to Homo erectus - David L. Roberts; Ivan Jarić; Stephen J. Lycett; Dylan Flicker; Alastair Key (Journal of Quaternary Science, 2023)
The presence of Homo floresiensis and Homo luzonensis in southeast Asia 90,000 to 60,000 years ago is considered surprising by many, and has been used to support their designation as unique species and the islands they were discovered on as refugia. Here, we statistically test the null hypothesis that H. floresiensis and H . luzonensis represent temporally uninterrupted occurrences relative to Homo erectus . We do this using the ‘surprise test’ for the exceptionality of a new record. Results demonstrate that H. floresiensis and H. luzonensis are not temporally distinct relative to H. erectus . Their late persistence should, therefore, not be considered surprising, they cannot reliably be inferred to be outside of H. erectus ’ temporal range, and – temporally – the islands of Luzon and Flores are not supported as refugia. Similarly, late H. erectus at Ngandong, Java, is not demonstrated to be temporally distinct relative to earlier, principally mainland‐Asian, H. erectus . Further, we demonstrate that substantial numbers of fossil discoveries would be needed before H. floresiensis and H. luzonensis are outside of H. erectus’ expected temporal range. If H. floresiensis and H. luzonensis are descended from H. erectus populations, our results point toward either geographic processes of allopatric speciation or behavioural processes leading to a sympatric speciation event.

Revisiting lithic edge characterization with microCT: multiscale study of edge curvature, re-entrant features, and profile geometry on Olduvai Gorge quartzite flakes - Danielle A. Macdonald; Tomasz Bartkowiak; Michał Mendak; W. James Stemp; Alastair Key; Ignacio de la Torre; Michał Wieczorowski (Archaeological and Anthropological Sciences, 2022)

Why invent the handle? Electromyography (EMG) and efficiency of use data investigating the prehistoric origin and selection of hafted stone knives - Alastair Key; Ian Farr; Robert Hunter; Anna Mika; Metin I. Eren; Samantha L. Winter (Archaeological and Anthropological Sciences, 2021)
For over 3 million years hominins held stone-cutting tools in the hand, gripping the portion of tool displaying a sharp cutting edge directly. During the late Middle Pleistocene human populations started to produce hafted composite knives, where the stone element displaying a sharp cutting edge was secured in a handle. Prevailing archaeological literature suggests that handles convey benefits to tool users by increasing cutting performance and reducing musculoskeletal stresses, yet to date these hypotheses remain largely untested. Here, we compare the cutting performance of hafted knives, ‘basic’ flake tools, and large bifacial tools during two standardized cutting tasks. Going further, we examine the comparative ergonomics of each tool type through electromyographic (EMG) analysis of nine upper limb muscles. Results suggest that knives (1) recruit muscles responsible for digit flexion (i.e. gripping) and in-hand manipulation relatively less than alternative stone tool types and (2) may convey functional performance benefits relative to unhafted stone tool alternatives when considered as a generalised cutting tool. Furthermore, our data indicate that knives facilitate greater muscle activity in the upper arm and forearm, potentially resulting in the application of greater cutting forces during tool use. Compared to unhafted prehistoric alternatives, hafted stone knives demonstrate increased ergonomic properties and some functional performance benefits. These factors would likely have contributed to the invention and widespread adoption of hafted stone knives during the late Middle Pleistocene.

Investigating interrelationships between Lower Palaeolithic stone tool effectiveness and tool user biometric variation: implications for technological and evolutionary changes - Alastair J.M. Key; Stephen J. Lycett (Archaeological and Anthropological Sciences, 2018)

Reassessing the production of handaxes versus flakes from a functional perspective - Alastair J.M. Key; Stephen J. Lycett (Archaeological and Anthropological Sciences, 2017)